Effect of humic acid on the sulfamethazine adsorption by functionalized multi-walled carbon nanotubes in aqueous solution: mechanistic study. Issue 18 (5th February 2016) - Yang, Quanquan; Li, Xiaogang; Chen, Guangcai; Zhang, Jianfeng; Xing, Baoshan
Abstract : The presence of humic acid (HA) inhibited sulfamethazine (SMZ) adsorption by three types of multi-walled carbon nanotubes via competitive interactions, molecular sieving, and pore blockage in solution (pH < 9). Abstract : Adsorption of humic acid (HA) and its effect on sulfamethazine (SMZ) adsorption by three types of multi-walled carbon nanotubes (MWCNTs) were investigated. The adsorption isotherms of HA and SMZ were well depicted by the Langmuir model ( R 2 > 0.99). HA adsorption onto MWCNTs increased as pH decreased and ionic strength increased, and decreased with increasing surface oxygen content of MWCNTs, implying that electrostatic and hydrophobic interactions were the main adsorption mechanisms. The presence of HA inhibited SMZ adsorption onto MWCNTs via competitive interactions, molecular sieving, and pore blockage. HA adsorbed on the MWCNTs surfaces also altered the electrostatic and hydrophobic interactions between SMZ and MWCNTs, decreasing the adsorption of SMZ. The results of micro-Fourier transform infrared spectroscopy suggested that π–π and hydrogen-bonding interactions of MWCNTs with SMZ and HA, and/or between SMZ and HA also play an important role in the adsorption process. The current findings shed light on evaluating the potential utilization of MWCNTs in antibiotics removal or analysis.